The Influence of Principal Leadership and Teacher Motivation on Student Parent Satisfaction in Schools Under The Daarut Tauhiid Rahmatan Lil’alamin Foundation - Fernando, Fernando; Sutjipto, Mohammad Riza (Jurnal Indonesia Sosial Sains, 2024)
Education is crucial for developing human resources and preparing for global competition. Parents play a vital role in this process, significantly influencing and making decisions about their children's education. Thus, educational institutions should consider parents as key customers in choosing schools. The Daarut Tauhiid Rahmatan Lil'Alamin Foundation operates schools at the elementary, middle, high, and vocational levels. This research aims to determine whether there is an influence of the principal's leadership and teacher motivation influence the level of customer satisfaction at the Daarut Tauhiid Rahmatan Lil'Alamin Foundation. This research uses quantitative methods and data collection techniques by distributing questionnaires whose validity and reliability have been tested. The sample in this research is the parents of students, with the total number of respondents that the researchers will take from the Daarut Tauhiid Rahmatan Lil'Alamin Foundation, namely 322 people. The research results show that the principal's leadership, teacher motivation, and customer satisfaction are in the "good" category. The principal's leadership and teacher motivation have a positive and significant influence with an influence value of 6.851 and 8.447. There is a simultaneous influence of principal leadership and teacher motivation on customer satisfaction, with an influence value of 166,572. The coefficient of determination is 0.511. That is, approximately 51.1% of the variability in customer satisfaction can be explained jointly by principal leadership and teacher motivation, while the remaining 48.9% can be distributed among other variables not included in this study. It is hoped that this research will contribute by exploring the factors that influence customer satisfaction, such as school principal leadership and teacher motivation. Therefore, the Foundation must improve to overcome this problem so that it does not happen again.